Vocational Orientation Education Management for Ethnic Minority Boarding School Students: A Case Study in Southern Vietnam - Nguyen, Van De; Nguyen, Thi Thu Hang; Ho, Van Thong; Le, Viet Ha; Duong, Thi Hang (International Journal of Learning, Teaching and Educational Research, 2026)
Vocational education is crucial in directing students toward suitable career trajectories while simultaneously cultivating vital skills, professional ingenuity, and motivation. In Vietnam’s Southern region, ensuring equitable access to vocational education for ethnic minority students in boarding schools is a critical concern. This study examines the administration of vocational education in ethnic minority boarding schools (EMBSs), with the objective of identifying current strengths, highlighting significant deficiencies, and recommending sustainable, culturally attuned strategies for enhancement. A quantitative survey design was utilized to collect data from 672 participants across 21 EMBSs, comprising 252 administrators and educators. Three structured questionnaires were employed to assess critical aspects of vocational education management, with data analyzed via descriptive statistics and reliability assessment utilizing Cronbach’s alpha. Results indicate robust performance in domains such as goal-setting, curriculum content, and financial planning. Nonetheless, considerable obstacles remain in the effective execution of activities, infrastructural constraints, and inadequate coordination among educational stakeholders. Moreover, contextual barriers—such as socioeconomic challenges and cultural diversity—significantly affect students’ vocational engagement and outcomes. The research emphasizes the significance of equity-focused, localized educational policies and provides pragmatic recommendations to augment institutional capacity, refine career guidance practices, and facilitate inclusive human resource development in Vietnam’s ethnic minority areas, thereby contributing to sustained educational reform. https://doi.org/10.26803/ijlter.25.3.27